Accumulation of Catechin and Proanthocyanidins in Black Poplar Stems After Infection by Plectosphaerella populi: Hormonal Regulation, Biosynthesis and Antifungal Activity - Ullah, Chhana; Unsicker, Sybille B.; Reichelt, Michael; Gershenzon, Jonathan; Hammerbacher, Almuth (Frontiers in Plant Science, 2019)
Flavan-3-ols including the monomeric catechin and the polymeric proanthocyanidins (PAs) are abundant phenolic metabolites in poplar (Populus spp.) previously described to protect leaves against pathogen infection. However, it is not known whether stems are also defended in this way. Here we investigated flavan-3-ol accumulation, activity and the regulation of formation in black poplar (P. nigra) stems after infection by a newly described fungal stem pathogen, Plectosphaerella populi, which forms canker-like lesions in stems. We showed that flavan-3-ol contents increased in P. populi infected black poplar stems over the course of infection compared to non-infected controls. Transcripts of leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR) genes involved in the last steps of flavan-3-ol biosynthesis were also up-regulated upon fungal infection indicating de novo biosynthesis. Amending culture medium with catechin and PAs reduced the mycelial growth of P. populi, suggesting that these metabolites act as anti-pathogen defenses in poplar in vivo. Among the hormones, salicylic acid (SA) was higher in P. populi infected tissues compared to the non-infected controls over the course of infection studied, while jasmonic acid (JA) and JA-isoleucine (JA-Ile) levels were higher than controls only at the early stages of infection. Interestingly, cytokinins (CKs) were also up-regulated in P. populi-infected stems. Poplar saplings treated with CK showed decreased levels of flavan-3-ols and SA in stems suggesting a negative association between CK and flavan-3-ol accumulation. Taken together, the sustained up-regulation of SA in correlation with catechin and proanthocyanidin accumulation suggests that this is the dominant hormone inducing the formation of antifungal flavan-3-ols during P. populi infection of poplar stems.